OPTIMASI SUHU DAN WAKTU MENGGUNAKAN RESPONSE SURFACE METHODOLOGY (RSM) PADA EKSTRAKSI OLEORESIN LIMBAH KULIT JERUK LEMON (Citrus limon (Linn.) Burm.F.) DENGAN BANTUAN GELOMBANG ULTRASONIK - Putra, I Gede Arie Mahendra; Widarta, I Wayan Rai; Ina, Putu Timur (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This study was aimed to determine the optimum temperature and extraction time of citrus lemon peel (Citrus limon (Linn.) Burm.F.) oleoresins by using Response Surface Methodology (RSM). The results showed that the optimum temperature and time of extraction with ultrasonic waves to produced oleoresins were 59,28ºC and 72,57 minutes. The extraction process with optimum temperature and time produced citrus lemon peel oleoresin with yield and refractive index respectively 32,47% and 1,4923. Meanwhile, the value of the density is equal to 1,3740 g/cm3 and the chemical compound was identified by GC-MS instrument. The component that was found in the citrus lemon peel oleoresin were 1-propanone, 1,3,6 Octratriene, Propanoic Acid, 2-Furancarboxaldehyde, 4-Vinyl-2-Methoxy-Phenol, 1-Pentene, Neryl Acetate, Geranic Acetate, ?-Bergamotene, Limonene, 2-Hexenal, 2-Bornanone, 2-Decyn-1-ol, Methyl Eugenol, Cis-P-Mentha-1(7),8-dien-2-ol, 1,4 Naphthalendione, Undecanal, Octadecanoic Acid, Pentadecanoic Acid, Decanoic Acid, 11-Octadecanoic Acid,GeranylButirate, Geranyl Propionate and 1,2-Benzenedicarboxylic Acid.